Investigation of the synthesis, activation, and isosteric heats of CO2 adsorption of the isostructural series of metal–organic frameworks M3(BTC)2 (M = Cr, Fe, Ni, Cu, Mo, Ru) - Wade, Casey R.; Dincă, Mircea (Dalton transactions : an international journal of inorganic chemistry, 2012)
The synthesis, activation, and heats of CO(2) adsorption for the known members of the M(3)(BTC)(2) (HKUST-1) isostructural series (M = Cr, Fe, Ni, Zn, Ni, Cu, Mo) were investigated to gain insight into the impact of CO(2)-metal interactions for CO(2) storage/separation applications. With the use of modified syntheses and activation procedures, improved BET surface areas were obtained for M = Ni, Mo, and Ru. The zero-coverage isosteric heats of CO(2) adsorption were measured for the Cu, Cr, Ni, Mo, and Ru analogues and gave values consistent with those reported for MOFs containing coordinatively unsaturated metal sites, but lower than for amine functionalized materials. Notably, the Ni and Ru congeners exhibited the highest CO(2) affinities in the studied series. These behaviors were attributed to the presence of residual guest molecules in the case of Ni(3)(BTC)(2)(Me(2)NH)(2)(H(2)O) and the increased charge of the dimetal secondary building unit in [Ru(3)(BTC)(2)][BTC](0.5).